Peer-to-Peer Lending Phenomenon in Indonesia - Yurilla Endah Muliatie; Mochamad Syaiful Arif; Rena Febrita Sarie (Universitas Serambi Mekkah, 2024)
According to a Financial Services Authority (OJK) report, funding through Fin Tech peer-to-peer (P2P) lending has grown significantly in the last five years. Fin Tech peer-to-peer (P2P) lending does provide many benefits to its users. Apart from the ease of making loans compared to conventional banks which provide many requirements, Fin Tech peer-to-peer (P2P) lending can provide solutions for its users to apply for loans with various conveniences. But currently many Indonesians cannot pay their bills. This can be seen from the bad credit ratio of various platforms. For various reasons and backgrounds, they are said to have failed to pay or not paid their bills. This is interesting because many literature studies explain the benefits of Fin Tech peer-to-peer (P2P) lending, but no one has written a scientific article from the user's side, let alone users who fail to fulfill their obligations to pay bills. Therefore, the author wants to conduct research from the consumer side, especially those who fail to fulfill their obligations. This research is qualitative research and the method that will be carried out is in-depth interviews. The long-term goal of this research is to educate readers to be wiser in using Fin Tech peer-to-peer (P2P) lending. The specific target is to serve as reference material for formulating policies on how Fin Tech peer-to-peer (P2P) lending can improve service quality not only for users who regularly pay their bills but also for users who fail to fulfill their obligations.